2003
DOI: 10.1016/j.mib.2003.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Identifying global regulators in transcriptional regulatory networks in bacteria

Abstract: The machinery for cells to take decisions, when environmental conditions change, includes protein-DNA interactions defined by transcriptional factors and their targets around promoters. Properties of global regulators are revised attempting to reach diagnostic explicit criteria for their definition and eventual future computational identification. These include among others, the number of regulated genes, the number and type of co-regulators, the different sigma-classes of promoters and the number of transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
444
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(463 citation statements)
references
References 63 publications
12
444
0
2
Order By: Relevance
“…As expected, the nucleotide salvage pathway (PID:5) highly responds to the environment where oxygen was present, while valine, leucine, and isoleucine metabolism pathway (PID:17) and alanine and which is designated as a global transcription factor in E. coli (32 ). A recent experiment confirmed that the activity of Lrp decreases as aerobiosis increases (33 ).…”
Section: Flux Rate Progression and Temporal Pathway Activationsupporting
confidence: 58%
“…As expected, the nucleotide salvage pathway (PID:5) highly responds to the environment where oxygen was present, while valine, leucine, and isoleucine metabolism pathway (PID:17) and alanine and which is designated as a global transcription factor in E. coli (32 ). A recent experiment confirmed that the activity of Lrp decreases as aerobiosis increases (33 ).…”
Section: Flux Rate Progression and Temporal Pathway Activationsupporting
confidence: 58%
“…In E. coli, the expression of 51% of all genes are under control of seven highly expressed global transcriptional regulators (CRP, FNR, IHF, FIS, ArcA, NarL and Lrp). Among these all but ArcA are employing negative feedback on their own synthesis 6,7 . However, all the six TFs bind weakly to the operators mediating the feedback compared with their binding to other specific sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Negative feedback is therefore commonly used to maintain homeostasis and to reduce the fluctuations in intracellular processes such as gene expression [3][4][5] . For example, nearly half of the B300 transcription factors (TFs) in Escherichia coli make use of negative feedback on their own expression 6,7 . However, the chemical noise that makes regulation necessary also limits the accuracy of feedback regulation 8 .…”
mentioning
confidence: 99%
“…Global transcription regulators have been defined as those TFs that have the ability to: regulate large number of genes belonging to diverse functional classes, control a complex regulatory cascade by both directly and indirectly effect expression of various cellular pathways and act on target promoters that use different sigma factors [46]. Based on this, seven global regulators in E. coli have been proposed, which control more than 50% of the genes in the entire transcriptional regulatory network.…”
Section: Dna Binding Tfs As Regulators Of Transcriptional Controlmentioning
confidence: 99%